PENGARUH MORALITAS INDIVIDU, PENGENDALIAN INTERNAL, DAN BUDAYA ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DALAM PENGELOLAAN KEUANGAN DESA (STUDI PADA KECAMATAN KANOR KABUPATEN BOJONEGORO) - Putri, Dila Cahyani; hartono, hartono; Hidayat, Esty Nur (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
This study aims to determine the effect of Individual Morality, Internal Control and Organizational Culture on Accounting Fraud Trends. The theory used in this study is the Fraud Triangle Theory. The population in this study were 100 village officials spread across 25 villages in Kanor District, Bojonegoro Regency. This study uses a purposive sampling technique. The sample was taken as many as 60 village officials in 15 villages in Kanor District, Bojonegoro Regency. Data collection is done by questionnaire method. Processing data using the SPSS version 22.0 application. The data analysis technique used is multiple linear regression analysis. The results of the study show that individual morality has a significantly positive effect on the tendency of accounting fraud, internal control and organizational culture in a positive way have a significant effect on the tendency of accounting fraud. Individual morality, internal control and organizational culture simultaneously have a significant positive influence on accounting fraud tendencies.